Organisasi Industri dalam Pendekatan Konsep Organisasi di Kota Surakarta - Miftahul Hariz; Ni Made Arsita Kusumadewi; Ivonia Auxiliadora F. Marcal; Muhammad Yasin (Jurnal Riset Ekonomi dan Akuntansi, 2023)
One of the problems facing change in organizations is trying to match change models with practical experience. The change model will be related to the change process. One of the famous batik industries is in the city of Surakarta, namely the Laweyan batik village. The objectives of this research are as follows: (1) Identify the causes of organizational changes occurring in the batik industry. (2) Identifying the impact of organizational change on the Batik Industry (3) Analyzing the ongoing organizational change process in the batik industry. This type of research uses a descriptive method with a case study approach. The data needed for this research are primary data and secondary data